(3GdCUhd GdYdejI hGdYedjI aj GdeMGSHI GdVQjHjI (B/s - (3GdNWjH, NGdO TMGOIs; (3WGaT, fGOjI aQjO s ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2008)
(3eONd dOQGSI VQjHI GdONd, NUGFU GdVQjHI Ydi GdONd, bGfhf GdVQjHI Ydi GdONd aj GdCQOf, eYGOdGJ GdVQjHI Ydi GdONd VQjHI GdONd ef cSH GdYed , GdVQjHI Ydi GdTQcGJ, GdVQjHI Ydi GdfeTBJ GdaQOjI, GdJbOjQ GdVQjHj Ydi GdHfhc hGdTQcGJ GdeGdjIhTQcGJ GdJCejf, GdJUQjM GdVQjHj hGdHjGfGJ GdhGLHI Ydi Gdecda HVQjHI GdONd JbOjegG, GdeSJfOGJ hGdMSGHGJ GdefJXeI JMUjd GdVQjHI hGdQOjGJ, GYJQGV hGSJFfGa bVGjG VQjHI GdONds
(3GdeQGLY U(B.335(3; GdedGMb U(B.337s
Keywords: (3GdVQGFH(B- (3eMGSHIs; (3GdVQjHI Ydi GdONds; (3GdeMGSHIs